Calcium Hydroxylapatite Dermal Filler for Treatment of Dorsal Hand Volume Loss: Results From a 12-Month, Multicenter, Randomized, Blinded Trial. Issue 1 (January 2018) - Goldman, Mitchel P.; Moradi, Amir; Gold, Michael H.; Friedmann, Daniel P.; Alizadeh, Kaveh; Adelglass, Jeffrey M.; Katz, Bruce E.
Abstract : BACKGROUND: Calcium hydroxylapatite (CaHA) microspheres suspended in a carrier gel is an opaque dermal filler that has been used to provide immediate volume correction in the dorsal hands. OBJECTIVE: To assess the safety and effectiveness of CaHA for the correction of volume loss in the hands up to 12 months. MATERIALS AND METHODS: This multicenter, controlled, single-blind study (NCT01832090) included 114 subjects randomized 3:1 to CaHA treatment and untreated control groups. Effectiveness was assessed by blinded investigators using the validated Merz Hand Grading Scale (MHGS). Subject-reported improvement was assessed using the Global Aesthetic Improvement Scale. Effects of treatment on hand function were also assessed. RESULTS: A total of 75% of subjects achieved ≥1-point improvement on the MHGS ( p < .0001) at 3 months (primary end point); this response was generally maintained through 12 months. Proportions of subjects reporting improvement ranged from 98% (3 months) to 86% (12 months). There were no clinically significant differences between control and CaHA-treated subjects in any hand function measure. Adverse events were generally expected, minor, short-lived, injection-related, and similar to those observed in previous CaHA clinical studies. CONCLUSION: Treatment with CaHA results in significant improvement in the appearance of the dorsal hand and is well tolerated. Abstract : Supplemental Digital Content is Available in the Text.